Experimental Study on the Shear Behavior of Bolted Concrete Blocks with Oblique Shear Test - Bo Meng; Hongwen Jing; Shengqi Yang; Yingchao Wang; Biao Li (Advances in Civil Engineering)
The shear behavior of concrete blocks reinforced by fully grouted bolts with different diameters was studied in this paper. More than 90 intact cubic samples (100 mm × 100 mm × 100 mm) with bolts ranging from 2 mm to 5 mm in diameter were tested at a constant stain rate of 0.5 mm/min. An oblique shear apparatus, which could simultaneously apply shear and normal force on tested samples at three slope angles (53°, 58°, and 63°) of a predetermined shear plane, was employed. The results indicate that the bolt has no evident influence on the shear behavior of intact concrete blocks at the prepeak shear strength stage. The bolt could significantly reduce the shear strength drop in the peak shear strength of the concrete block and contribute to reserving the residual shear strength of concrete blocks, especially at steep slope angles of the shear failure plane. The shear resistance provided by the bolt to the concrete block at the residual shear slip stage has a positive relationship with the diameter. The bolt with a larger diameter inflected in the vicinity of the shear failure plane of concrete block at the postpeak shear strength stage; additional normal force and direct shear resistance could still be persistently provided. Two empirical equations of the apparent cohesion and apparent internal angle of the bolted concrete block were obtained by linear regression considering rb, which is the ratio of the cross-sectional area of the bolt to that of the bolted concrete block.